SAT0644 Is ankle involvement important in rheumatoid arthritis?. (15th June 2017) - Enache, L; Mogosan, C; Popescu, C; Gutoiu, G; Codreanu, C
Abstract : Background: The ankles may be affected by rheumatoid arthritis (RA). In daily evaluation of RA patients, the ankles are often neglected by clinical examinations, while composite activity scores do not include them Objectives: The aim of the study is to assess the inflammatory lesions in RA ankles, regarding frequency and possible correlation with activity disease Methods: The study included 76 RA patients fulfilling the 2010 ACR/EULAR classification criteria. In every patient we recorded clinical ankle involvement (ankle swelling and/or tenderness on physical examination); both ankles were evaluated by gray scale (GS) and Power Doppler (PD) ultrasound examination, graded from 0–3. In each joint we assessed: tibio-talar joint (TT); tibialis anterior (TA) tendon; extensor hallux (EH) and extensor digitorum (ED) tendons; talo-navicular joint (TN); tibialis posterior (TP) tendon; flexor digitorum (FD) and flexor hallux (FH) tendons; peroneus brevis (PB) and longus (PL) tendons; Achilles tendon (AT); subtalar joints (SJ; posterior, lateral, medial recesses); plantar fascia (PL). We recorded the following abnormalities: synovitis, tenosynovitis, bursitis, entesopathy and rupture. Activity scores (DAS28, DAS44, SDAI), inflammatory markers (ESR, CRP), serology (FR, ACPA) and HAQ were also assessed Results: The mean age was 57.2±14.2 years; 88% were women; mean disease duration was 12.2±9.2 years; 56.6% had symptomatic ankles; 81.6% had ultrasound ankle abnormalities. The most frequent ultrasound pathology encountered was ST synovitis (56.6%), followed by TT synovitis (48.7%), TN synovitis (38.2%), TP tenosynovitis (30.3%), PL tenosynovitis (15.8%). Ultrasound abnormalities were recorded in 93% of the symptomatic ankle patients and in 66.7% of the asymptomatic ankle patients (p=0.008). Overall, 43% had positive PD signals, but the prevalence of positive PD signals was significantly higher in symptomatic ankle patients than in asymptomatic ankle patients (60.5% compared to 21.2%, p=0.011). Statistically significant correlations were found between ultrasound inflammatory pathology (synovitis and tenosynovitis), activity disease markers and quality of life (Table 1 ). Conclusions: Musculoskeletal ultrasound detected a high prevalence of inflammatory abnormalities in rheumatoid arthritis ankles, in both symptomatic and asymptomatic patients, while power Doppler signal was present mostly in symptomatic patients. The ultrasound pathology was highly correlated with activity disease markers and quality of life References: M Backhaus, G-R Burmester, T Gerber et al., Guidelines for musculoskeletal ultrasound in rheumatology, Ann Rheum Dis 2001, ; 60:641–649. M Alsuwaidi, B Ehrenstein, M Fleck et al., Ankle Joint in Rheumatoid Arthritis. An Ultrasound Study Using High Resolution- and Clour Doppler Ultrasound, 2013 ACR/ARHP Annual Meeting, Abstract No 1969. Disclosure of Interest: None declared